ZZ/ZW Sex Chromosomes in the Madagascar Girdled Lizard, Zonosaurus madagascariensis (Squamata: Gerrhosauridae) - Kostmann, Alexander; Kratochvíl, Lukáš; Rovatsos, Michail (Genes, 2022)
Scincoidea, the reptilian clade that includes girdled lizards, night lizards, plated lizards and skinks, are considered as a lineage with diversity in sex-determining systems. Recently, the hypothesis on the variability in sex determination in skinks and even more the absence of sex chromosomes in some of them has been rivalling. Homologous, evolutionary stable XX/XY sex chromosomes were documented to be widespread across skinks. However, sex determination in the other scincoidean families is highly understudied. ZZ/ZW sex chromosomes have been identified only in night lizards and a single species of plated lizards. It seems that although there are different sex chromosome systems among scincoidean lineages, they share one common trait: they are mostly poorly differentiated and often undetectable by cytogenetic methods. Here, we report one of the exceptions, demonstrating for the first time ZZ/ZW sex chromosomes in the plated lizard Zonosaurus madagascariensis. Its sex chromosomes are morphologically similar, but the W is clearly detectable by comparative genomic hybridization (CGH), suggesting that the Z and W chromosomes highly differ in sequence content. Our findings confirm the presence of female heterogamety in plated lizards and provides novel insights to expand our understanding of sex chromosome evolution in scincoidean lizards.
Keywords: Sex Chromosomes; rDNA loci; pohlavní chromozomy; srovnávací genomová hybridizace; C-banding; Sex Determination Processes; telomeres; sex determination; ZZ/ZW; cytogenetics; Madagascar; Lizards; ještěři; FISH; sex chromosomes; Animals; lidé; ženské pohlaví; Humans; zvířata; Comparative Genomic Hybridization; Madagaskar; CGH; procesy určující pohlaví; Female; karyotype